MODERASI KEPEMILIKAN INSTITUSIONAL TERHADAP HUBUNGAN PERENCANAAN PAJAK NILAI PERUSAHAAN DENGAN - Sartika, Dewi; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the tax avoidance to the firm value with the institutional ownership as the moderation on the automotive company and component which are listed in Indonesia Stock Exchange during the 2011-2013 periods. The research samples have been selected by using purposive sampling technique and 12 automotive components (36 firm year) which meet the criteria. The regression equation is done by using Moderated Regression Analysis (MRA) as the examiner whether the moderating variabel can strengthen or weaken the correlation among these independent variabels to the dependent variabel. Based on the result of the multiple regressions analysis as the analysis technique with the significance level of 5%, the result of the research shows that: The first hypothesis stated that tax evasion has influence to the firm value it shows a negative correlation. The second hypothesis stated that the institutional ownership does not have any influence to the firm value it shows the negative correlation, and the third hypothesis stated that institutional ownership has positive moderation to the correlation of tax evasion to the firm value.Keywords: Tax Planning, Institutional Ownership, and Firm Value